Macrophages and pulmonary fibrosis: a bibliometric and visual analysis of publications from 1990 to 2023 - Min, Yi; Wu, Lifei; Xu, Cheng; Han, Wen; Yin, Zhi; Pan, Xu; Sun, Luyao; Zhang, Jinrong; Wan, Guoqiang; Zhou, Tongxin (Frontiers in Medicine, 2024)
Background The role of macrophages in the symptomatic and structural progression of pulmonary fibrosis (PF) has garnered significant scholarly attention in recent years. This study employs a bibliometric approach to examine the present research status and areas of focus regarding the correlation between macrophages and PF, aiming to provide a comprehensive understanding of their relationship. Methodology The present study employed VOSviewer, CiteSpace, and Microsoft Excel software to visualize and analyze various aspects such as countries, institutions, authors, journals, co-cited literature, keywords, related genes, and diseases. These analyses were conducted using the Web of Science core collection database. Results A comprehensive collection of 3,479 records pertaining to macrophages and PF from the period of 1990 to 2023 was obtained. Over the years, there has been a consistent increase in research literature on this topic. Notably, the United States and China exhibited the highest level of collaboration in this field. Through careful analysis, the institutions, authors, and prominent journals that hold significant influence within this particular field have been identified as having the highest publication output. The pertinent research primarily concentrates on the domains of Biology and Medicine. The prevailing keywords encompass pulmonary fibrosis, acute lung injury, idiopathic pulmonary fibrosis, and others. Notably, TGFβ1, TNF, and CXCL8 emerge as the most frequently studied targets, primarily associated with signaling pathways such as cytokine–cytokine receptor interaction. Additionally, cluster analysis of related diseases reveals their interconnectedness with ailments such as cancer. Conclusion The present study employed bibliometric methods to investigate the knowledge structure and developmental trends in the realm of macrophage and PF research. The findings shed light on the introduction and research hotspots that facilitate a more comprehensive understanding of macrophages and PF.